Bibliometric Analysis of Global Research on Perinatal Palliative Care - Wang, Yiting; Shan, Chunjian; Tian, Yingying; Pu, Congshan; Zhu, Zhu (Frontiers in Pediatrics, 2022)
Objectives: The aim of this study was to perform a bibliometric analysis of publications related to perinatal palliative care to identify scientific output and research trends at a global level. Methods: The Web of Science Core Collection database was searched to retrieve publications focusing on perinatal palliative care published between 2001 and 2020. All retrieved publications were identified by title and abstract for their relevance to perinatal palliative care. These eligible publications were extracted from the following data: title, abstract, year, keywords, author, organization, journal and cited literature. VOSviewer software was used to conduct bibliographic coupling, coauthorship, and cooccurrence analyses and to detect publication trends in perinatal palliative care research. Results: A total of 114 publications concerning perinatal palliative care were included. The annual number of publications has increased dramatically in recent years. The United States has made the largest contribution to this field with the majority of publications (68, 59.6%) and citations (1091, 70.5%) and with close collaborations with researchers in Canada, Portugal and Australia. Wool C and her institution, York College of Pennsylvania, are the respectively most prolific author and institution in this field, publishing 18 papers (15.8%). Journal of Palliative Medicine is the leading and main journal in this field. According to the cooccurrence network analysis, five main research topics were identified: the candidates for PPC, service models and forms, framework components, parental perspectives and satisfaction, and challenges and needs of health care providers. Conclusions: The findings of this bibliometric study illustrate the current state and global trends of perinatal palliative care for the past two decades, which will help researchers determine areas of research focus and explore new directions for future research in this field.